Effect of Mercuric Chloride (HgCl2) Stress on DNA, RNA and Enzymes Vigna mungo L. Seedlings - Mohapatra, Mamata (International Journal of Applied Sciences and Biotechnology, 2022)
At elevated concentrations all heavy metals are potentially toxic. Effects of Mercuric Chloride on the morphological parameters such as DNA, RNA and Enzymes were analysed during investigation on 10th day in seedlings of Vigna mungo L., All parameters exhibited reduced trend with increase in HgCl2 concentrations when compared to control plants but the enzyme activities increased. This indicates that, the seedlings are in the process of increase in tolerance to HgCl2 treatment. Metal toxicity affects crop yields, soil biomass and fertility. Int. J. Appl. Sci. Biotechnol. Vol 10(1): 16-20.